Flora saxícola da formação Cártica Sete Lagoas, Minas Gerais - Vera Lúcia Ferreira (2020)
The presence of carbonate rocks determines a specific type of relief, "Karst", from Serbo-Croatian language, means "limestone field". Karst areas are characterized by the formation of caves, canyons, rocky walls, dolines and residual massifs due to vertical and underground drainage over soluble rocks. They are characterized by small areas or different extensions to the surrounding environments. Their microhabitats create favourable environmental conditions for the establishment of plant species. Karst rock outcrops are considered areas of species richness and endemism. However, direct anthropic (e.g. mining) or indirect (e.g. invasive species) actions are constant threats to the diversity of its flora. Eugenius Warming (1841-1924) introduced the world to the peculiar and extraordinary karst flora of the unknown province of Lagoa Santa in Minas Gerais. His work Florula lagoensis contributes to the reduction of Linnean (Taxonomic) and Wallacean (Occurrence) deficits due to the high number of collections in the region. The massive Gruta do Baú (municipality of Pedro Leopoldo) and Gruta da Lapinha (Lagoa Santa), part of the Sete Lagoas Formation, comprise terrestrial islands, which belong to the geological formation of the Bambuí group. We hope that the results might help to subsidize actions to manage and conserve the flora of the representative karsts of the Sete Lagoas formation. In the first chapter, the floristic survey of the exposed rock areas located in the massif was carried out. The species data were obtained from the Flora do Brasil 2020 and CNCFlora database. We registered 124 vascular plant species, distributed among 45 families and 92 genera. The richest families were Orchidaceae (14 spp.), Bromeliaceae (11 spp.), and Piperaceae (10 spp.), whereasfor the monilophytes were Pteridaceae (five spp.), Aspleniaceae and Polypodiaceae (three spp. each). Most species have a wide distribution, occurring in the Cerrado, Atlantic Forest and Caatinga biomes (54 spp.), followed by species in the Cerrado and Atlantic Forest (33 spp.). In contrast, only a few species are exclusive to a single biome (12 spp. in the Cerrado and 13 spp. in the Atlantic Forest). None of the species is exclusive of the Caatinga Biome. Invasive and ruderal species represented 19%, a significant result. A total of 73% (91) of the species collected in the two massifs are included in the list of species collected by Warming (Florula lagoensis). The rare species Rodriguezia brachystachys Rchb.f. & Warm. and Ruehssia virgultorum (E.Fourn.) F.Esp.Santo & Rapini were collected in Pedro Leopoldo after a long period of time without registration. Five species are on the list of threatened species, that associated with the percentage of species “Not Evaluated” (78%), indicate the necessity of preventive measures regarding the preservation of the limestone outcrops’ vegetation. In the second chapter, the list of species in chapter I was used to characterize the microhabitats, life forms and their correlation of massif species. The microhabitats were classified as: soil island, crevice, fissure, exposed rock, and epiphyte. The microhabitat cleft had the largest number of species (54 spp.), followed by soil island (20 spp.), and epiphyte (17 spp.). In a total of 124 registered species, 57 are considered common to both massifs. Species richness was greater in the Gruta do Baú with 95 species collected and 38 classified as exclusives. Cracks create favourable conditions which facilitate the establishment of the largest number of species. The most common life forms, in terms of the biological spectrum, were phanerophytes 26% (33 spp.), followed by hemicryptophytes 20% (25 spp.), and campesites 19% (24 spp.). Despite the low floristic similarity between the massifs, the floristic similarity among the microhabitats was high. The results demonstrate that each massif is distinct, with a peculiar flora highly influenced by heterogeneity (microhabitats) and organized according to the available resources (niches). The heterogeneous and fragmented landscapes of the Karst studied indicate the essential requirement to preserve large outcrop areas of the Sete Lagoas Formation once they are fundamental to the conservation of biodiversity on a broader scale.